2015
DOI: 10.1227/neu.0000000000000599
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Variable Extent of Anterior Clinoidectomy With Intradural and Extradural Approaches

Abstract: Quantitative comparative evaluation provides details of exposure and surgical ease with both techniques. We promote hybrid/EDAC technique for vascular pathologies because of better anatomic orientation. Extradural clinoidectomy is the preferred technique for midline cranial neoplasia. An awareness of different variations of clinoidectomy can prevent dependency on any particular approach and facilitate flexibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 27 publications
1
28
0
1
Order By: Relevance
“…I agree with Wilson et al that "entrapment neuropathies commonly occur as nerves pass beneath rigid ligamentous structures," 8 as this is also the case with ulnar nerve entrapment under the HUA (i.e., the cubital tunnel syndrome). However, I am reluctant to accept their suggestion of "a much rarer scenario involving compression of a nerve by a hypertrophied muscle secondary to overuse."…”
Section: Can Muscle Hypertrophy Cause Entrapment Neuropathy?supporting
confidence: 74%
See 4 more Smart Citations
“…I agree with Wilson et al that "entrapment neuropathies commonly occur as nerves pass beneath rigid ligamentous structures," 8 as this is also the case with ulnar nerve entrapment under the HUA (i.e., the cubital tunnel syndrome). However, I am reluctant to accept their suggestion of "a much rarer scenario involving compression of a nerve by a hypertrophied muscle secondary to overuse."…”
Section: Can Muscle Hypertrophy Cause Entrapment Neuropathy?supporting
confidence: 74%
“…In their series of 168 UNE patients, they found a prevalence of 5.4%, which was significantly lower (p < 0.001) than the 15.5% reported in 634 control arms from previous MRI and cadaver studies. 8 The authors concluded that the presence of the anconeus epitrochlearis muscle seems an unlikely causative factor for UNE. Furthermore, they argued that its presence may actually have a protective role against the UNE.…”
Section: Can Muscle Hypertrophy Cause Entrapment Neuropathy?mentioning
confidence: 99%
See 3 more Smart Citations